Corrective Surgery for Palpebral Coloboma in a Feline Using the Technique of Transposition of the Lip Commissure - Girondi, Giulia Brambila; Krebs, Carlos Otávio Eggres; Farencena, Fernanda Iensen; Corrêa, Luís Felipe Dutra (Acta Scientiae Veterinariae, 2021)
Background: Eyelid coloboma is considered a disease caused by failure in eye development during the first semester of pregnancy. In felines, its prevalence occurs in the upper eyelids, temporal region, and bilaterally. Coloboma, whether to a large or small extent, can lead to keratoconjunctivitis sicca and trichiasis, situations that can give rise to secondary ulcerative keratitis. The only corrective method is blepharoplasty. The current work aims to report the case of corrective surgery for eyelid coloboma in a feline with a successful postoperative period, in order to corroborate the effectiveness of the technique. We also report a finding of persistent pupillary membrane. Case: A 7-month-old male feline, no defined breed, was analyzed with a purulent mucus secretion and signs of discomfort in the right eye. After the ophthalmic screening, the presence of a coloboma was identified, which occupied approximately 50% of the size of the upper eyelid, in the temporal-dorsal region of the right eye. The cat had already undergone an enucleation of the left eye due to a perforation arising from ulcerative keratitis. Together with coloboma, the presence of blepharospasm, trichiasis, keratoconjunctivitis sicca, and secondary ulcerative keratitis were diagnosed. The presence of persistent pupillary membrane was also observed, a rare condition in the feline species. To confirm the ulcer, the fluorescein test was applied and treatment with antibiotic eye drops and lacrimomimetics (tear film replacements) drops was administered until the day of surgery, one week later. Concomitant with the institution of treatment prior to surgery, blood was collected for complementary pre-surgical tests such as blood count and biochemistry, which demonstrated satisfactory results. Corrective surgery was then instituted by the technique of transposing the labial commissure, described in 2010, which consists of replacing the colobomatous tissue with a flap from the oral region. To ensure quality in the postoperative period, the use of the Elizabethan collar, oral antibiotics, analgesics, anti-inflammatory drugs, and cleaning with 0.9% saline solution around the sutures were prescribed. The first return appointment occurred on the day after the operation and further appointments were made weekly for one month. As the animal did not present any complications in the healing process, the spacing between the follow-up appointments was increased. After 2 months, the animal demonstrated a palpebral reflex and a pleasant appearance. Discussion: The results were similar to those described by the author of the technique, as there was no recurrence of hair in contact with the cornea, the flap mucosa became efficient in terms of the quality in lubricating the fibrous tunic, and an appearance acceptable to the owner was achieved. It is also reported that, different from previous studies, the technique was able to correct palpebral coloboma without any complications during the post-surgical process. In all previously published works, some type of setback was reported, such as dehiscence of the suture of the oral region, dehiscence of the transposed suture, superficial necrosis of the flap, deformation of facial folds, excessive graft retraction, and return of trichiasis in the pre-existing medial region. It is inferred, then, that the use of this technique for correction of eyelid coloboma longer than 1/3 should be indicated.